Suriname : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues explores ways for strengthening the current fiscal framework in Suriname and considers options for a new fiscal anchor. The paper provides an overview of mineral natural resources and their importance for the budget. It also lays out the current framework for fiscal planning and budget execution in Suriname and discusses the analytical underpinnings of modernizing it to make it more robust. The paper also presents estimates of long-term sustainability benchmarks based on the IMF's policy toolkit for resource-rich developing countries. Suriname's fiscal framework can be strengthened through a fiscal anchor rooted in the non-resource primary balance. Given the size of fiscal adjustment required to bring the non-resource primary balance in line with the long-term sustainability benchmark, a substantial transition period is needed to implement it. The IMF Staff's adjustment scenario-designed to put public debt on the downward path-closes the current gap by less than half, implying that adjustment would need to continue beyond the 5-year horizon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet